ONCE BITTEN, TWICE SHY: UPGRADING TRADITIONAL MARKETS AS A STRATEGY TO PROMOTE COMPLIANCE WITH SAFETY PROTOCOLS OF, AND BEAT, COVID-19 HANDS-DOWN - Olajuyin, Oyebanji Anthony; Oluwadiya, Kehinde Sunday; Olajuyin, Ademola Busayo; Olajuyin, Adebola Ayotomiwa; Ogunboyo, Femi Ojo; Olatunya, Oladele Simeon; Adegbiji, Atilade Waheed; Olajide, Toye Gabriel (International Journal of Research -GRANTHAALAYAH, 2021)
The traditional market has characteristic features that could make effectivecompliance with Covid-19 safety protocols in the market a difβicult task toaccomplish, thus, predisposing the market and the entire community to theresurgence of Covid-19 pandemic. This paper described the factors in the tra-ditional markets that could make effective compliance with Covid-19 safetyprotocols a mission impossible. The paper emphasizes the need to upgradethe traditional market as a strategy to eliminate those innate factors that mil-itate against effective compliance with Covid-19 safety protocols. The studywas a prospective, comparative analysis of compliance with Covid-19 safetyprotocols in the Traditional Markets (TM) and Modern Markets (MM) in EkitiState, Southwest Nigeria. The results showed that the traditional markets weremajorly the open-air types with propensity for overcrowding, clustering, row-diness and long business hours. The compliance scores across all the Covid-19safety protocols and especially physical distancing were very poor in the tra-ditional markets compared with the modern markets. This re-afβirms the exis-tence of anti-compliance factors of Covid-19 safety protocols in the traditionalmarkets. There is therefore the need to upgrade the traditional markets witha view to facilitate compliance with the Covid-19 safety protocols and subduethe resurgence of Covid-19 pandemic in Ekiti State, Southwest Nigeria.